2023
DOI: 10.1158/2159-8290.cd-22-1441
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Selective FGFR Inhibitors in FGFR-Driven Urothelial Cancer

Abstract: Several FGFR inhibitors are approved or in clinical development for the treatment of FGFR-driven urothelial cancer, and molecular mechanisms of resistance leading to patient relapses have not been fully explored. We identified 21 FGFR-driven urothelial cancer patients treated with selective FGFR inhibitors and analyzed post-progression tissue and/or circulating tumor DNA (ctDNA). We detected single mutations in the FGFR tyrosine kinase domain in seven (33%) patients (FGFR3 N540K, V553L/M, V555L/M, E587Q; FGFR2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Exon 18 truncating mutations are associated with prolonged stable disease in some instances 32 . In general, de novo FGFR kinase domain mutations showed low response to pemigatinib, which was not unexpected as secondary mutations in the kinase domain represent a mechanism of acquired resistance 21 , 22 , 24 , 33 36 ; however, we note that exceptional cases of clinical benefit did occur, including one patient with FGFR1 K656E and one patient with molecular brake mutation FGFR1 N546K. To systematically characterize the sensitivity of a diverse array of FGFR1–FGFR3 SNVs to FGFR inhibition in the clinic, we compiled available data from these patients from multiple FGFR inhibitor trials.…”
Section: Discussionmentioning
confidence: 83%
“…Exon 18 truncating mutations are associated with prolonged stable disease in some instances 32 . In general, de novo FGFR kinase domain mutations showed low response to pemigatinib, which was not unexpected as secondary mutations in the kinase domain represent a mechanism of acquired resistance 21 , 22 , 24 , 33 36 ; however, we note that exceptional cases of clinical benefit did occur, including one patient with FGFR1 K656E and one patient with molecular brake mutation FGFR1 N546K. To systematically characterize the sensitivity of a diverse array of FGFR1–FGFR3 SNVs to FGFR inhibition in the clinic, we compiled available data from these patients from multiple FGFR inhibitor trials.…”
Section: Discussionmentioning
confidence: 83%
“…This is important for FGFR, whose mutations have a different impact on therapy response, but may be even more relevant for HER2; while many clinical results are reported in patients with high HER IHC expression, some HER2 mutations may render treatment useless, regardless of expression status [78]. Furthermore, genomic profiling performed repeatedly could also allow for the early detection of resistance mechanisms within the molecular target itself or parallel pathways, such as PI3K-mTOR mutations that confer resistance to FGFR inhibitors [53] and HER2-targeting agents [80].…”
Section: Discussionmentioning
confidence: 99%
“…Facchinetti et al analysed the post-progression tumour DNA of UC patients with FGFR alterations treated with FGFR inhibitors and found that, in 38% of cases, resistance was related to the acquisition of one or more mutations in the FGFR tyrosine kinase domain. Interestingly, in 52% of cases, resistance was linked to the acquisition of new mutations in the PI3K-mTOR pathway [53].…”
Section: Fgfr Alterationsmentioning
confidence: 99%
“…Indeed, anti-FGFR agents are known to cause particular toxicities related to the inhibition of the FGFR pathway that takes part in various physiological functions. The most common adverse event is hyperphosphatemia, with a prevalence of 60-76% of treated patients, related to the FGFR1 receptor that is present in proximal renal tubule cells [94]. Although the management of this condition is widely known, the correction of the phosphate imbalance very often results in a dose reduction and sometimes leads to treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%